Backdoor pathway for dihydrotestosterone biosynthesis: Implications for normal and abnormal human sex development. Issue 4 (19th November 2012) - Fukami, Maki; Homma, Keiko; Hasegawa, Tomonobu; Ogata, Tsutomu
<x xml:space="preserve">Abstract</x> We review the current knowledge about the "backdoor" pathway for the biosynthesis of dihydrotestosterone (DHT). While DHT is produced from cholesterol through the conventional "frontdoor" pathway via testosterone, recent studies have provided compelling evidence for the presence of an alternative "backdoor" pathway to DHT without testosterone intermediacy. This backdoor pathway is known to exist in the tammar wallaby pouch young testis and the immature mouse testis, and has been suggested to be present in the human as well. Indeed, molecular analysis has identified pathologic mutations of genes involved in the backdoor pathway in genetic male patients with undermasculinized external genitalia, and urine steroid profile analysis has argued for the relevance of the activated backdoor pathway to abnormal virilization in genetic females with cytochrome P450 oxidoreductase deficiency and 21‐hydroxylase deficiency. It is likely that the backdoor pathway is primarily operating in the fetal testis in a physiological condition to produce a sufficient amount of DHT for male sex development, and that the backdoor pathway is driven with a possible interaction between fetal and permanent adrenals in pathologic conditions with increased 17‐hydroxyprogesterone levels. These findings provide novel insights into androgen biosynthesis in both physiological and pathological conditions. Developmental Dynamics 242:320–329, 2013. © 2012 Wiley Periodicals, Inc.